2020
DOI: 10.1093/neuonc/noaa280
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian approach for diagnostic accuracy of malignant peripheral nerve sheath tumors: a systematic review and meta-analysis

Abstract: Background Malignant peripheral nerve sheath tumors (MPNST) carry a dismal prognosis and require early detection and complete resection. However, MPNSTs are prone to sampling errors and biopsies or resections are cumbersome and possibly damaging in benign peripheral nerve sheath tumor (BPNST). This study aimed to systematically review and quantify the diagnostic accuracy of noninvasive tests for distinguishing MPNST from BPNST. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…Bayesian inference adds a small amount of informative priors that can stabilize the analysis without overwhelming data ( 24 ), as opposed to the frequentist methods that express the initial uncertainty with a prior distribution. Bayesian bivariate meta-analyses have advantages in estimating the heterogeneity among studies and pooled effect, especially when the number of studies included is small ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian inference adds a small amount of informative priors that can stabilize the analysis without overwhelming data ( 24 ), as opposed to the frequentist methods that express the initial uncertainty with a prior distribution. Bayesian bivariate meta-analyses have advantages in estimating the heterogeneity among studies and pooled effect, especially when the number of studies included is small ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…A threshold of 3.5 for SUVmax has often been proposed as the ideal threshold [21][22][23]. A recent meta-analysis pooled individual level patient data from 11 different study populations and found a threshold of 3.5 provided the highest sensitivity (0.99) and acceptable specificity (0.75) [24]. Arguments against using this threshold often consisted of the low specificity it offered.…”
Section: Optimal Pet Algorithmmentioning
confidence: 99%
“…Altogether, the results from these studies will provide a framework that may enable optimal diagnostic algorithms to be formulated. This study only assessed the diagnostic accuracy of 18 F-FDG PET-CT. A recently published metaanalysis reported that although conventional MRI yields varying degrees of accuracy, some studies have shown high accuracies in functional MRI [24]. Though further research is required on this modality, reducing the need for 18 F-FDG PET-CT may diminish radiation exposure that accumulates due to numerous follow-up scans necessary in NF1 patients prone to tumorigenesis.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the quotient of the SUV index tissue/liver (T/L) may eliminate the difference between scanners, but the optimal value of the T/L index has not been defined. The use of repeated PET-CT with a delay increases the diagnostic value but also in parallel the costs and exposes the patient to ionizing radiation [92,93].…”
Section: Treatment Of Mpnst Associated With Nf1 Radiological Diagnosismentioning
confidence: 99%